Treatment of TiO2 surface for deposition of gold nanoparticles from colloidal suspension. (18th June 2015) - Rehacek, V; Hotovy, I; Vojs, M
Abstract: In this paper, experimental knowledge is presented on the deposition of gold nanoparticles from a colloidal solution on the surfaces of TiO2 prepared on silicon wafers. Important parameters, such as TiO2 surface hydrophilization and functionalization by silane coupling agent (3-mercapto-propyl-tri-metoxy-silane) were investigated in order to obtain TiO2 surface with optimum properties for the immobilization of Au nanoparticles with a close-packed structure.